Principal-Agent Governance Mechanism in an Emerging Biofuels Supply Chain in USA - Pandey, Vivek; Shanoyan, Aleksan; Peterson, H Christopher; Ross, R. Brent (Asian Journal of Agriculture and Rural Development, 2013)
This article analyzes the incentives and compensation problems faced by cellulosic ethanol producer and logging firms and the consequent impact on the organization of the wood based cellulosic ethanol industry in the US. The success of this relationship is central to setting up the biofuel industry in Michigan and in the US at large. The study utilizes the theoretical framework of institutional economics and uses case methodology to discuss potential problems arising from information asymmetry. Theoretical results indicate that the specification contract under the principal-agent framework is of limited utility due to’ metering’ problem when the principal contracts with multiple agents for the supply of feedstock. Alternative arrangements including joint ventures have the potential to provide close to first best solutions.